Psychological interventions countering misinformation in social media: A scoping review - Gwiaździński, Paweł; Gundersen, Aleksander B.; Piksa, Michal; Krysińska, Izabela; Kunst, Jonas R.; Noworyta, Karolina; Olejniuk, Agata; Morzy, Mikołaj; Rygula, Rafal; Wójtowicz, Tomi; Piasecki, Jan (Frontiers in Psychiatry, 2023)
The rise of social media users and the explosive growth in misinformation shared across social media platforms have become a serious threat to democratic discourse and public health. The mentioned implications have increased the demand for misinformation detection and intervention. To contribute to this challenging and urgent problem, we are presenting a systematic scoping review of psychological interventions countering misinformation in social media. The review was conducted to (i) compare the effectiveness of the interventions, (ii) define the interventions taxonomy, and (iii) provide guidelines for the development of effective interventions. A systematic search in three bibliographic databases (PubMed, Embase, and Scopus) and additional searches in Google Scholar and reference lists resulted in identifying 3461 records, 75 of which met the eligibility criteria for the inclusion in the final review. The psychological interventions identified during the review can be classified into four categories: UX Shift, Educational, Nudging, and Inoculation, and then into subcategories within these. Most of the studied interventions were not implemented and tested in a real social media environment but under strictly controlled settings or online crowdsourcing platforms. The presented feasibility assessment of implementation insights expressed qualitatively and with numerical scoring could guide the development of future interventions that can be successfully implemented on social media platforms.